Free convection flow of Brinkman type fluid through an cosine oscillating plate / Siti Noramirah Ibrahim ... [et al.] - Ibrahim, Siti Noramirah; Mohamad, Ahmad Qushairi; Lim, Yeou Jiann; Shafie, Sharidan; Zakaria, Muhammad Najib (2021)
In this study, heat transfer on the unsteady flow of Brinkman type fluid model induced by free convection phenomenon is investigate. The flow is considered to be bounded by a vertical oscillating plate. The dimensional governing equations, as well as the initial and oscillating boundary conditions, are reduced to dimensionless forms using appropriate dimensionless variables. The Laplace transformation is employed on the resulting dimensionless equations to solve for the closed form solution of temperature and velocity fields. The graphical results illustrating the temperature and velocity profiles under the consequences of related parameters such as Prandtl number, Grashof number, Brinkman type fluid parameter, phase angle, and time are displayed.